(untitled) (Bangladesh Journal of Botany, 2010)
Effects of Agri Fos 400 (Mono and di-potassium phosphanate), a fungicide widely used on tomatoes grown in greenhouses in Turkey against Phytophthora infestans were studied on the morphology and viability of tomato (Lycopersicon esculentum Mill.) pollens. The fungicide was applied on tomato plants at recommended dosage (4 ml/l water) and double the recommended dosage (8 ml/l water). The fungicide caused changes in the morphological structures of pollens. Some pollen morphological structures that are not observed in the control group were encountered in the pollens due to application of Agri Fos 400 in equatorial view at 8 ml/l and in polar view at 4 ml/l. Level of pollen viability decreased as the dosage increased. Key words: Fungicide; Phytophthora infestans; Tomato; Pollen morphology; Viability DOI: 10.3329/bjb.v38i2.5134 Bangladesh J. Bot. 38(2): 115-118, 2009 (December)